Small surfactant-like peptides can drive soluble proteins into active aggregates - Zhou Bihong; Xing Lei; Wu Wei; Zhang Xian-En; Lin Zhanglin (Microbial Cell Factories, 2012)
Abstract Background Inactive protein inclusion bodies occur commonly in Escherichia coli (E. coli) cells expressing heterologous proteins. Previously several independent groups have found that active protein aggregates or pseudo inclusion bodies can be induced by a fusion partner such as a cellulose binding domain from Clostridium cellulovorans (CBDclos) when expressed in E. coli. More recently we further showed that a short amphipathic helical octadecapeptide 18A (EWLKAFYEKVLEKLKELF) and a short beta structure peptide ELK16 (LELELKLKLELELKLK) have a similar property. Results In this work, we explored a third type of peptides, surfactant-like peptides, for performing such a "pulling-down" function. One or more of three such peptides (L6KD, L6K2, DKL6) were fused to the carboxyl termini of model proteins including Aspergillus fumigatus amadoriase II (AMA, all three peptides were used), Bacillus subtilis lipase A (LipA, only L6KD was used, hereinafter the same), Bacillus pumilus xylosidase (XynB), and green fluorescent protein (GFP), and expressed in E. coli. All fusions were found to predominantly accumulate in the insoluble fractions, with specific activities ranging from 25% to 92% of the native counterparts. Transmission electron microscopic (TEM) and confocal fluorescence microscopic analyses confirmed the formation of protein aggregates in the cell. Furthermore, binding assays with amyloid-specific dyes (thioflavin T and Cong red) to the AMA-L6KD aggregate and the TEM analysis of the aggregate following digestion with protease K suggested that the AMA-L6KD aggregate may contain structures reminiscent of amyloids, including a fibril-like structure core. Conclusions This study shows that the surfactant-like peptides L6KD and it derivatives can act as a pull-down handler for converting soluble proteins into active aggregates, much like 18A and ELK16. These peptide-mediated protein aggregations might have important implications for protein aggregation in vivo, and can be explored for production of functional biopolymers with detergent or other interfacial activities.